Aldaulactone – An Original Phytotoxic Secondary Metabolite Involved in the Aggressiveness of Alternaria dauci on Carrot - Courtial, Julia; Hamama, Latifa; Helesbeux, Jean-Jacques; Lecomte, Mickaël; Renaux, Yann; Guichard, Esteban; Voisine, Linda; Yovanopoulos, Claire; Hamon, Bruno; Ogé, Laurent; Richomme, Pascal; Briard, Mathilde; et al. (Frontiers in Plant Science, 2018)
Qualitative plant resistance mechanisms and pathogen virulence have been extensively studied since the formulation of the gene-for-gene hypothesis. The mechanisms involved in the quantitative traits of aggressiveness and plant partial resistance are less well-known. Nevertheless, they are prevalent in most plant-necrotrophic pathogen interactions, including the Daucus carota-Alternaria dauci interaction. Phytotoxic metabolite production by the pathogen plays a key role in aggressiveness in these interactions. The aim of the present study was to explore the link between A. dauci aggressiveness and toxin production. We challenged carrot embryogenic cell cultures from a susceptible genotype (H1) and two partially resistant genotypes (I2 and K3) with exudates from A. dauci strains with various aggressiveness levels. Interestingly, A. dauci-resistant carrot genotypes were only affected by exudates from the most aggressive strain in our study (ITA002). Our results highlight a positive link between A. dauci aggressiveness and the fungal exudate cell toxicity. We hypothesize that the fungal exudate toxicity was linked with the amount of toxic compounds produced by the fungus. Interestingly, organic exudate production by the fungus was correlated with aggressiveness. Hence, we further analyzed the apolar fungal exudates using HPLC, and correlations between the observed peak intensities and fungal aggressiveness were measured. One observed peak was closely correlated with fungal aggressiveness. We succeeded in purifying this peak and NMR analysis revealed that the purified compound was a novel polyketide with a 10-membered benzenediol lactone, that we named ‘aldaulactone’. We used a new automated image analysis method and found that aldaulactone was toxic to in vitro cultured plant cells at those concentrations. The effects of both aldaulactone and fungal organic extracts were weaker on I2-resistant carrot cells compared to H1 carrot cells. Taken together, our results suggest that: (i) aldaulactone is a new phytotoxin, (ii) there is a relationship between the amount of aldaulactone produced and fungal aggressiveness, and (iii) carrot resistance to A. dauci involves mechanisms of resistance to aldaulactone.